Willmore Flow of Networks. Issue 1 (17th December 2018) - Garcke, Harald; Menzel, Julia; Pluda, Alessandra
Abstract: We consider networks of curves in the plane moving according to the L 2 –gradient flow of the elastic energy. We prove short time existence in the case of networks composed of three curves that are required to meet at one or two triple junctions. As a variation of the result we additionally impose that they form angles of 120 degrees at the triple junction(s).